Plasmacytoma as a Mimicker of Colonic Carcinoma in an Elderly Man - Sara Mathew George; Eman Ali Aljufairi; Nisha Chandran; Sayed Ali Isa Almahari (Case Reports in Pathology)
Multiple myeloma is a neoplastic proliferation of monoclonal plasma cells. Although it is usually restricted to the bone marrow, extraskeletal spread in the form of localised extramedullary collections of malignant plasma cells (plasmacytomas) can occur. However, gastrointestinal tract involvement in multiple myeloma is rare and overt gastrointestinal bleeding from plasmacytoma is uncommon. We report a case of colonic plasmacytoma which presented with bleeding per rectum and was initially misdiagnosed as colonic neuroendocrine carcinoma. Later the patient presented with recurrence of the colonic mass along with multiple lytic bone lesions. The diagnosis of colonic plasmacytoma with progression into multiple myeloma was given. We also discuss here the diagnostic difficulty of plasma cell neoplasms in small biopsies of the colon.